2013
DOI: 10.1371/journal.pone.0064246
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Retinal Degeneration in Aged Wild Type and APPswe/PS1ΔE9 Mice by Bone Marrow Transplantation

Abstract: Alzheimer's disease (AD) is an age-related condition characterized by accumulation of neurotoxic amyloid β peptides (Aβ) in brain and retina. Because bone marrow transplantation (BMT) results in decreased cerebral Aβ in experimental AD, we hypothesized that BMT would mitigate retinal neurotoxicity through decreased retinal Aβ. To test this, we performed BMT in APPswe/PS1ΔE9 double transgenic mice using green fluorescent protein expressing wild type (wt) mice as marrow donors. We first examined retinas from con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 79 publications
0
33
0
Order By: Relevance
“…In line with the above findings, numerous studies examining the retinas of sporadic and transgenic animal models of AD have reported Aβ deposits, vascular Aβ, pTau, and paired helical filament-tau (PHF-tau), often in association with RGC degeneration, local inflammation (i.e., microglial activation), and impairments of retinal structure and function (11,39,40,42,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61). These studies, which included a variety of transgenic rat and mouse models, as well as the sporadic rodent model of AD, Octodon degus, demonstrated abundant Aβ deposits, mainly in the innermost retinal layers (RGCs and NFL) (40,42,45,49,52,54,57).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…In line with the above findings, numerous studies examining the retinas of sporadic and transgenic animal models of AD have reported Aβ deposits, vascular Aβ, pTau, and paired helical filament-tau (PHF-tau), often in association with RGC degeneration, local inflammation (i.e., microglial activation), and impairments of retinal structure and function (11,39,40,42,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61). These studies, which included a variety of transgenic rat and mouse models, as well as the sporadic rodent model of AD, Octodon degus, demonstrated abundant Aβ deposits, mainly in the innermost retinal layers (RGCs and NFL) (40,42,45,49,52,54,57).…”
Section: Introductionmentioning
confidence: 57%
“…These studies, which included a variety of transgenic rat and mouse models, as well as the sporadic rodent model of AD, Octodon degus, demonstrated abundant Aβ deposits, mainly in the innermost retinal layers (RGCs and NFL) (40,42,45,49,52,54,57). Furthermore, several publications, including ours, have reported a positive response to therapy in reducing retinal Aβ plaque burden in transgenic (ADtg) murine models, often reflecting the reaction observed in the respective brains (40,48,51,52,56,60). To visualize retinal Aβ pathology in vivo, we had previously developed a noninvasive retinal amyloid imaging method for rodent ADtg models, using curcumin as a contrast agent (40,51).…”
Section: Introductionmentioning
confidence: 60%
“…However, retinal plaques were not detected in another model, the non-Tgwt mice. In this model, Yang et al (10) confirmed a twofold increase in microglia, prominent inner retinal Aβ, paired helical filament-tau, and decreased retinal ganglion cell layer neurons. They also showed that bone marrow transplantation has a protective action against retinal degeneration, resulted from alterations in the immune function and oxidative stress.…”
Section: Animal Modelsmentioning
confidence: 79%
“…Among the family of matrix metalloproteinases (MMP), MMP-9 and MMP-8 are important for the migration of microglia during embryogenesis [3]. Expressed MHC class II [41] Highly expressed MHC class II [21] Expressed MHC class II [42] Neurotoxicity Produced pro-inflammatory cytokines [43] Produced pro-inflammatory cytokines [44] Produced pro-inflammatory cytokines (in brain) [45] Increased ROS [16,46] Reduced ROS [16] Reduced ROS (in brain) [47] Produced nitric oxide [48] Expressed the inducible form of nitric oxide synthase (in brain) [49] Produced nitric oxide [42] Phagocytosis Dead photoreceptors and cell debris (dead cells in brain) [50,51] Unclear Dead photoreceptors and cell debris [50] Living stressed photoreceptors (living neurons in brain) [52,53] Unclear Unclear Amyloid deposits clearance Impaired Aβ clearance and facilitated Aβ deposition [16] Increased Aβ clearance [14,16] Increased Aβ clearance [54] Neuroprotection Produced neurotrophic factors [55] Unclear Produced neurotrophic factors [15] Unclear Unclear Produced anti-inflammatory cytokines [56] Vascularization Promoted the formation of CNV (VEGF, PDGFβ, and ICAM) [55] Pathological neovascularization (IL-1β) [44,57] Promoted the formation of CNV [58] Unclear Physiological neovascularization [59] Unclear…”
Section: Origin and Distribution Of Microglia During Development Ys Amentioning
confidence: 99%
“…These cells transfer from the bone marrow to the blood, enter the CNS, and generate microglia in special conditions. In many studies, BM-derived microglia have been identified in the CNS of BM chimera mice that received irradiation [14][15][16]. Nevertheless, it is difficult to avouch the necessity of irradiation or BM transplantation for the migration and generation of BM-derived cells.…”
Section: Introductionmentioning
confidence: 99%